Exploring inter-organizational relationships in historically black colleges and universities: cooperation, coordination, and collaboration - Elmore, Jessica Lee (Kansas State University, 2015)
Institutional advancement is a constant challenge for leaders at institutions of higher education. The continued threat to historically black college and universities (HBCU) survival, due to the lack of resources they need to operate and compete, is at the forefront of concerns for many HBCU presidents and supporters. Research suggests that to have success in acquiring more resources, universities will need to work with their alumni associations and foundations. The purpose of this qualitative, multi-case study was to contribute to the limited research on the relationships among HBCU leaders responsible for growing resources. Numerous aspects contribute to increasing alumni giving and this study will contribute to that knowledge. The discussion of inter-organizational relationships and how the processes of cooperation, coordination, and collaboration transpire should be a part of the dialogue. Exploration of these relationships and processes can highlight possible solutions and deficiencies in the success of institutional advancement. Sites for this study were purposefully selected to examine these inter-organizational relationships. Data included in-depth interviews and related documents and artifacts. Thirty patterns and three themes emerged from the data analysis. The three themes include an understanding that (a) “working together” enacts cooperation, coordination, and collaboration; (b) human capital and organizational structures affect coordination and the ability to reach goals; and (c) the goal for increased resource capacity focuses the efforts of cooperation, coordination, and collaboration. This study extends the discussion to looking at inter-organizational relationships as another perspective to enhance resources. This investigation also introduces dialogue about alumni association and foundation volunteerism as an important component in developing effective solutions. The understandings portrayed in the identified themes will help university officials, practitioners, advancement volunteers, and supporters of higher education enhance their institutional advancement strategies and help set forth norms for productive behaviors.
Keywords: ​Historically Black Colleges and Universities; Higher education fundraising; Inter-organizational association; Higher education administration; Alumni giving; Fund raising; Black Studies (0325); Educational leadership (0449); Higher Education (0745)